The physiological demands of horseback mustering when wearing an equestrian helmet - Taylor, N. A. S.; Caldwell, J. N.; Dyer, R. (European Journal of Applied Physiology, 2008)
The hottest months on northern Australian cattle stations are from September to November, and it is during these months that horseback cattle mustering occurs. Stockmen wear clothing that restricts heat loss, and protective helmets have recently been introduced. Anecdotal evidence points to the possibility that helmets may increase the probability of developing heat illness, or reducing workplace performance. In this project, we quantified the working (thermal) environment on such cattle stations, and measured the metabolic demands on, and concurrent physiological strain in stockmen during mustering, whilst wearing an equestrian helmet. During horseback work, the average heart rate was 102.0 beats/min (SD 14.0), with almost 90% of the time (238 min) spent working at intensities <50% of the heart rate reserve. The projected metabolic heat production during mustering ranged between 178 and 333 W (women), and between 212 and 542 W (men). The average core temperature was 37.6°C, while the mean skin temperature averaged 34.1°C. It was concluded that the working environment is, on average, thermally uncompensable during the mustering season. However, horseback mustering per se is a relatively low-intensity activity, interspersed with short periods of high-intensity work. This activity level was reflected within core temperatures, which rarely climbed above values associated with light-moderate exercise. Thus, whilst the climatic state was uncompensable, stockmen used behavioural strategies to minimise the risk of heat illness. Finally, it was observed that the helmet, though unpleasant to wear, did not appear to increase thermal strain in a manner that would disadvantage stockmen.